Study of the natural radioactivity of selected samples of the soil of Al-Nada district in Najaf - Hady, Heiyam Najy; Kadim, Shahad Fadel (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
This study reported activity concentration of 238 U, 232 Th, 40 K in 50 soil samples AL-Nada district - Najaf Governorate - Iraq Measurement using gamma ray spectrometer NaI (TI) (3x3). The activity concentrations of natural radionuclides are found to range from (31.319  Bq.Kg-1 to (1.1583 Â± 0.0821) Bq.Kg-1with average (11.851 0.281) Bq.Kg-1 of uranium 238U.  From (1.117Â±0.048)  Bq.Kg-1 to  (23.948 ) Bq.Kg-1  with an  average of  (6.283 0.148 ( Bq.Kg-1 for thorium 232Th,.from(13.592Â±0.282) Bq.Kg-1 to (705.834 6.179) Bq.Kg-1 and average (265.494 1.445) Bq.Kg-1 potassium40K , equivalent radium  from (12.489 0.328) Bq.Kg-1 to (84.199 1.911) Bq.Kg-1 and average (40.078 0.564) Bq.Kg-1 , internal  hazard index from (0.039) Bq.Kg-1to( 0.256) Bq.Kg-1 and average( 0.139) Bq.Kg-1,external hazard index ranged from( 0.033) Bq.Kg-1 to (0.227) Bq.Kg-1 and average( 0.108) Bq.Kg-1 values  either of absorbed dose in air from (5.728 0.150) nGy/h to (42.667 0.901) nGy/h and average(19.914 0.264) nGy/h  , internal annual effective dose from (0.028 0.0005) mSv/y to (0.209 0.0044) mSv/y and average (0.097 0.0013) mSv/y, external annual effective dose from (0.0070 0.0001) mSv/y to (0.0523 0.001) mSv/y  and average (0.0244 0.0003) mSv/y The results were found to be comparable or lower than similar global reporting data. According to this, research soil The area can be considered to have a normal level of natural background radiation